Proceedings of the IEEE Intelligent Vehicles Symposium 2000 (Cat. No.00TH8511)
DOI: 10.1109/ivs.2000.898395
|View full text |Cite
|
Sign up to set email alerts
|

DOLPHIN for inter-vehicle communications system

Abstract: Inter-Vehicle Communications (IVC) technology for Group Cooperative Driving has been studied by Association of Electronic Technology for Automobile Traffic and Driving (JSK) since the date of 1980 in Japan. The study of the IVC technology has been focussed on the communication protocol. This paper proposes DOLPHIN (Dedicated Omni-purpose inter-vehicle communication Linkage Protocol for HIghway automatioN) and presents its performance evaluation results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(39 citation statements)
references
References 2 publications
0
38
0
1
Order By: Relevance
“…The results of their study showed that both AODV and General Packet Radio Service (GPRS) demonstrate grave performance limitations in terms of significantly reduced packet delivery ratio due to extremely high mobility of nodes. Table V shows the comparative review of evaluated ad-hoc routing protocols designed for vehicular communication systems such as mobility-centric data dissemination algorithm (MDDV) [48], anchor bus street and traffic-aware routing (ABSTAR) protocol [49], vehicle-assisted data delivery (VADD) [50], Dedicated Omni-purpose inter-vehicle communication Linkage Protocol for HIghway automatioN (DOLPHIN) for inter-vehicle communications system [51], Position-based multi-hop broadcast (PMB) [52], robust vehicular routing (ROVER) and distributed robust geocast (DRG) protocols [53], BROADcast COMMunication (BROADCOMM) protocol [35], distributed vehicular broadcast (DV-CAST) [54].…”
Section: Vanets Ad-hoc Routing Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of their study showed that both AODV and General Packet Radio Service (GPRS) demonstrate grave performance limitations in terms of significantly reduced packet delivery ratio due to extremely high mobility of nodes. Table V shows the comparative review of evaluated ad-hoc routing protocols designed for vehicular communication systems such as mobility-centric data dissemination algorithm (MDDV) [48], anchor bus street and traffic-aware routing (ABSTAR) protocol [49], vehicle-assisted data delivery (VADD) [50], Dedicated Omni-purpose inter-vehicle communication Linkage Protocol for HIghway automatioN (DOLPHIN) for inter-vehicle communications system [51], Position-based multi-hop broadcast (PMB) [52], robust vehicular routing (ROVER) and distributed robust geocast (DRG) protocols [53], BROADcast COMMunication (BROADCOMM) protocol [35], distributed vehicular broadcast (DV-CAST) [54].…”
Section: Vanets Ad-hoc Routing Protocolsmentioning
confidence: 99%
“…The design and development of efficient IEEE 802.11p-based DSRC wireless access system that will support efficient and reliable congestion control (CC) techniques is required for effective dissemination of time-critical safety messages in vehicular networks. Many studies have been carried out to validate and evaluate the performance of congestion control techniques [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. Several approaches have been employed by researchers for performance evaluation of wireless communication systems such as vehicular wireless communication system with simulation and field test methodology as the two most widely used approaches.…”
Section: Congestion Control Techniques In Inter-vehicle Communicationmentioning
confidence: 99%
“…The vehicle dynamics are similar to a car-following model. The WNS supports IEEE 802.11x [4] and DOLPHIN [79] as MAC protocols.…”
Section: Traffic Simulators In Vanets Researchmentioning
confidence: 99%
“…The main purpose of the Next generation Intelligent Transport Systems (ITS) is the safe driving, one example of such systems is Advanced Vehicle Control and Safety System (AVCSS) [7]. The goal of the AVCSS is to improve the safety and convenience of driving, optimize energy consumption by having smooth traffic flow and increase the efficiency of transport industry.…”
Section: Background Work On Inter Vehicle Communication Protocolsmentioning
confidence: 99%